Carbon dioxide storage and sequestration potential of trees in the University of the Philippines Cebu - Tabornal, Krissa Joy L. (Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2022)
Urban green spaces are valuable infrastructures that promote ecological stability and positive wellbeing of citizens. However, very few studies have explored carbon stocks of urban vegetation in the Philippines. Despite the carbon neutrality goal of the educational sector, carbon management remains ineffective in many universities. Conducting carbon offset potential assessment is a useful guide in formulating carbon management plans. The CO2 emission of the University of the Philippines (UP) Cebu in 2018 to 2020 has already been computed. It is imperative to take the next climate action by calculating the carbon offset potential of the trees on campus. This study aimed to calculate the CO2 storage of trees at the UP Cebu campuses; calculate the annual CO2 sequestration potential of these trees; and estimate CO2 emission from landscape management. A tree inventory in Lahug and South Road Properties campuses was conducted. The diameter at breast height of trees was used in allometric equations to compute biomass and equivalent CO2 capture. The CO2 emissions from landscape management were estimated through interviews. There are 403 trees in UP Cebu campuses that cumulatively store 911,241.56 kgCO2e and annually sequesters 37,988.38 kgCO2e. The annual total CO2 emission from using landscape equipment is 271.45 kgCO2e. Results imply that the annual sequestration is not enough to compensate for the university emissions during the business-as-usual scenarios. To achieve carbon neutrality from biological sequestration alone, 16,000 more trees need to be planted. This is not feasible so the university should consider other reduction strategies, such as electricity saving initiatives, carpooling, and recycling. Pterocarpus indicus, Mangifera indica, and Vitex parviflora are recommended species for tree planting initiatives. This study is a useful model for institutions to calculate their carbon offset potential and use the assessment to improve their greenhouse gas mitigation strategies.